Basic Health Assessment of Orphans at Al Walidaturrahmah Orphanage to Prevent Stunting in Samarinda (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
In the world, many children become orphans and have to live in orphanages for various reasons. They often face various health challenges due to limited access to balanced nutrition, healthcare services, and psychosocial support. Their health and well-being are a shared responsibility between the government and the community, including local community organizations. Aisyayah, one of Muhammadiyah's women's organizations, plays an active role in supporting this initiative by managing orphanages.  The problem that arises is that the children come from orphans and the poor; they tend to have health problems before being placed in the orphanage. In addition, diverse lifestyles affect the health conditions of the orphanage children. The community services aimed to detect health problems among the orphans and provide basic care. The community service method was conducted at Al Walidaturrahmah orphanage, which involved a health checkup that included blood pressure, Body Mass Index (BMI), and hemoglobin levels to assess the health and growth of the children in the orphanage. The results showed that 45 children, consisting of 16 boys and 29 girls, were included. During the blood pressure examination, 23 children had normal blood pressure, 5 children had mild blood pressure elevation, and 17 children had stage 1 hypertension. In the BMI examination, there were 5 children in the thin category, 29 children were normal weight, 6 children were overweight, and 5 children were obese. Twenty-nine girls had menstruated, 22 had normal hemoglobin levels, 5 had mild to moderate anemia, and 17 had normal hemoglobin levels. The result shows some unhealthy conditions among the orphans that need follow-up regularly.